Intellectual disabilities. (November 2016) - Simpson, Neill; Mizen, Lindsay; Cooper, Sally-Ann
Abstract: All doctors should expect to have some patients with intellectual disabilities. People with intellectual disabilities have very high rates of physical and mental ill-health, and co-morbidity is typical. Gastro-oesophageal reflux disorder, epilepsy, sensory impairments and injuries are all more common than in the general population. Choking and aspiration are frequent and can cause death. Developmental disorders, psychosis and behavioural problems are common. Problem behaviours are multifactorial and can be a sign of other mental or physical disorders or distress. Some associated conditions are related to the causes of a person's intellectual disabilities (e.g. 'behavioural phenotypes') and can benefit from treatment interventions. There are thousands of causes of intellectual disabilities, and often the cause is unknown despite comprehensive assessment. Assessments take longer than for people who do not have intellectual disabilities, and must involve relatives and paid carers as well as the person with intellectual disabilities. A biopsychosocial–developmental framework is useful. Avoid 'diagnostic overshadowing', in which symptoms of medical conditions are incorrectly attributed to the person's intellectual disabilities and left untreated. People with intellectual disabilities face many barriers in accessing the healthcare they need, and more proactive approaches by health professionals are required.